The Pathogenesis of Diabetes Mellitus by Oxidative Stress and Inflammation: Its Inhibition by Berberine - Ma, Xueling; Chen, Zhongjun; Wang, Le; Wang, Gesheng; Wang, Zihui; Dong, XiaoBo; Wen, Binyu; Zhang, Zhichen (Frontiers in Pharmacology, 2018)
A substantial knowledge on the pathogenesis of diabetes mellitus (DM) by oxidative stress and inflammation is available. Berberine is a biologically active botanical that can combat oxidative stress and inflammation and thus ameliorate DM, especially type 2 DM. This article describes the potential of berberine against oxidative stress and inflammation with special emphasis on its mechanistic aspects. In diabetic animal studies, the modified levels of proinflammatory cytokines and oxidative stress markers were observed after administering berberine. In renal, fat, hepatic, pancreatic and several others tissues, berberine-mediated suppression of oxidative stress and inflammation was noted. Berberine acted against oxidative stress and inflammation through a very complex mechanism consisting of several kinases and signaling pathways involving various factors, including NF-κB (nuclear factor-κB) and AMPK (AMP-activated protein kinases). Moreover, MAPKs (mitogen-activated protein kinases) and Nrf2 (nuclear factor erythroid-2 related factor 2) also have mechanistic involvement in oxidative stress and inflammation. In spite of above advancements, the mechanistic aspects of the inhibitory role of berberine against oxidative stress and inflammation in diabetes mellitus still necessitate additional molecular studies. These studies will be useful to examine the new prospects of natural moieties against DM.